CREATION OF AUTOMATED SOFTWARE FOR ONLINE SALES IN BOOKSTORES (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
This article examines the creation of online trading platforms, including book trading, their software interface and its capabilities, the functions of existing devices in the software interface and their analysis, the software tools used in creating an electronic trading platform and their capabilities. In particular, as an example, instructions for creating and using an electronic trading platform dealing with the sale of one book are given.